2020
DOI: 10.1186/s12941-020-00391-x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus nasal carriage among janitors working in hospital and non-hospital areas: a comparative cross-sectional study

Abstract: Background Nasal colonization of Methicillin-resistant Staphylococcus aureus (MRSA) plays a key role in the epidemiology and pathogenesis of both healthcare-associated and community-acquired MRSA infections in various populations. Screening of MRSA nasal colonization is important in the prevention and control of infection and may provide useful information to guide antimicrobial therapy. This study aimed to determine nasal carriage of MRSA, its antimicrobial susceptibility pattern, and associated factors among… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[ 18 ] and similar to the results of Abie et al . and Zhu et al .,[ 19 20 ] whereas inconsistent with Gushiken et al . [ 21 ]…”
Section: Resultsmentioning
confidence: 94%
“…[ 18 ] and similar to the results of Abie et al . and Zhu et al .,[ 19 20 ] whereas inconsistent with Gushiken et al . [ 21 ]…”
Section: Resultsmentioning
confidence: 94%
“…MRSA is a significant global bacterial pathogen in various countries including Saudi Arabia [5,7,8]. The incidence of non-hospital personnel (NHP)-and hospital personnel (HP)-acquired MRSA carriers has increased since 2000 [9,10]. MRSA is a normal flora of the upper respiratory tract, particularly the nose and nasopharynx, and frequently leads to both NHP and HP carriers [10].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of non-hospital personnel (NHP)-and hospital personnel (HP)-acquired MRSA carriers has increased since 2000 [9,10]. MRSA is a normal flora of the upper respiratory tract, particularly the nose and nasopharynx, and frequently leads to both NHP and HP carriers [10]. Methicillin resistance is attributed to the expression of the mecA gene, which alters penicillin-binding protein (PBP-2) to PBP-2a, resulting in a loss of target affinity [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the janitor's awareness of contact precautions was limited in our institution. Previous studies reported cases of meticillin-resistant Staphylococcus aureus isolated from hospital janitors as opposed to from non-hospital janitors, indicating the possibility of the janitors being vectors of the multidrug resistant strains [ 7 , 8 ]. Our case highlights that improving awareness of contact precautions among janitors is an important factor in preventing the outbreak of multidrug-resistant strains.…”
mentioning
confidence: 99%